(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The director is a person, a leader, a leader, who, on the basis of an in-depth study of the social conditions and the subjective factors arising from it, transforms the interests and goals of the people and society into a single artistic form. It is the director’s main task to choose which theme to stage in the theater, how many ideas to share, how to inspire the performers.